Violencia de género y su influencia en el entorno familiar de una adolescente - Valencia Hernandez, Nancy Elizabeth (2020)
In this investigation a case study was presented on a teenage victim of sexual abuse, it should be noted that the abuser was his political uncle. Having as presumptive diagnosis according to the ICD criteria10 problems related to the alleged sexual abuse by a person within the primary support group. The main objective is to determine how this type of gender violence influences the adolescent family environment and a psychotherapist scheme or with a systematic approach. To carry out this study, a psychological tool is needed for the drafting of the medical history, in addition to the psychometric test that serves as an aid to the therapist to determine a diagnosis with more feasibility and accuracy, using the FF-SIL test and the The human figure of Machober. The final result of this research is the application of the technique of therapeutic intervention as are the circular questionnaires to achieve a better relationship in the family's emotional bonds.